Post-glacial sedimentary processes and slope instabilities off Nordnesfjellet, Lyngenfjorden, northern Norway - Hegstad, Sigrun Maret Kvendbø (UiT Norges arktiske universitet, 2014)
The Lyngen- and Storfjorden system, Troms County, northern Norway, is surrounded by an alpine landscape, partly with steep mountain sides. Parts of the ~700 m high mountain Nordnesfjellet, on the eastern side of the fjord, are currently moving downslope, and could in the event of sudden failure generate tsunami waves which would affect low-lying areas within a larger region. The main objective of this study is to integrate multi-proxy analyses of five sediment cores, swath bathymetry and high-resolution seismic data from one NNE-SSW oriented basin of Lyngenfjorden, off Nordnesfjellet, with the purpose of reconstructing mass-wasting activity in the past. The fjord sides in the study area are up to >30o steep and irregular with depressions, escarpments and furrows of various sizes and ‘freshness’. These features are interpreted to be slide scars and gullies, respectively, related to slope failures. The central parts of the up to 270 m deep basin are generally smooth. However, an up to 8 m high step, crossing almost the entire fjord width, defines the northern limit of a relatively irregular seafloor in the southern part of the study area. Furthermore, sediment-lobe areas are visible as undulating seafloor on the western and eastern sides of the basin. The high-resolution seismic data reveal that the uppermost <12 ms two-way-travel time (~9 m) are composed of acoustically transparent sediments with few, discontinuous reflections. Deposits causing a chaotic reflection pattern underlie this package within the areas of irregular and undulating seafloor, where also several acoustically well stratified sediment blocks (up to ~300 x 300 x 10 m3) are identified. The acoustically chaotic deposits are e.g. debris flows or turbidites, whereas the blocks are either run-out blocks embedded in the debris flows or slide blocks. The mass-transport deposits are stacked together in several complexes which cover and partly erode into glaciomarine sediments. It is assumed that these complexes were deposited during a relatively ...